A mammalian arginine/lysine transporter uses multiple promoters. - Finley, K D (1995)
The mCAT-2 gene encodes a Na(+)-independent cationic amino acid (AA) transporter that is inducibly expressed in a tissue-specific manner in various physiological conditions. When mCAT-2 protein is expressed in Xenopus oocytes, the elicited AA transport properties are similar to the biochemically defined transport system y+. The mCAT-2 protein sequence is closely related to another cationic AA transporter (mCAT-1); these related proteins elicit virtually identical cationic AA transport in Xenopus oocytes. The two genes differ in their tissue expression and induction patterns. Here we report the presence of diverse 5' untranslated region (UTR) sequences in mCAT-2 transcripts. Sequence analysis of 22 independent mCAT-2 cDNA clones reveals that the cDNA sequences converge precisely 16 bp 5' of the initiator AUG codon. Moreover, analysis of genomic clones shows that the mCAT-2 gene 5'UTR exons are dispersed over 18 kb. Classical promoter and enhancer elements are present in appropriate positions 5' of the exons and their utilization results in regulated mCAT-2 mRNA accumulation in skeletal muscle and liver following partial hepatectomy. The isoform adjacent to the most distal promoter is found in all tissues and cell types previously shown to express mCAT-2, while the other 5' UTR isoforms are more tissue specific in their expression. Utilization of some or all of five putative promoters was documented in lymphoma cell clones, liver, and skeletal muscle. TATA-containing and (G+C)-rich TATA-less promoters appear to control mCAT-2 gene expression. The data indicate that the several distinct 5' mCAT-2 mRNA isoforms result from transcriptional initiation at distinct promoters and permit flexible transcriptional regulation of this cationic AA transporter gene.